Strategic Planning and Its Impact on the Development of University and Technical Education Institutions (An Applied Study on the Faculties of the University of Tripoli (Journal of human and social sciences, 2026)
The importance of this study is that it highlights the effective role which played by strategic planning as the backbone of strategic management, whose significantly contributes to the development of education, and also this study aimed to identify the reality of strategic planning in these institutions by answering the questions: What is the reality of strategic planning in these institutions? What is the availability of financial and human resources necessary for the implementation of the strategic planning?To achieve its objectives, the study used the descriptive analytical method, utilizing a questionnaire that was distributed to the study sample which represented in deans and heads of scientific affairs in some colleges at the University of Tripoli. The statistical package (SPSS) was used to analysis the data. The study found that the strategic planning in the undergraduate education mainly depends on the extent of the college administrations' are convinced of the importance of strategic planning and how applied their planning. The results also showed the role played by financial and human resources in the success of the strategic planning process.A number of recommendations can be provided by this study, which is the importance of dissemination of the culture of planning in general and strategic planning in particular among faculty members and staff within the faculties. The administrations of these colleges must commit to implementing, monitoring and supervising the strategic plans. The recommendations also emphasized the necessity of providing sufficient financial resources to rationalize strategic plans as well as continuous training of human resources to carry out the tasks and responsibilities of strategic planning.Finally, the challenges facing higher education institutions require the adoption of a strategic plan based on a set of specific qualitative and quantitative objectives that can be implemented within a specific period of time. This will eventually lead to the development of university education programs and curricula as a means of ensuring the quality of education and achieving benefits to contribute to the sustainable development of society.
Keywords: : Strategic Planning; Institutions Development; University Education; Technical Education; Tripoli University